2013
DOI: 10.1186/bcr3425
|View full text |Cite
|
Sign up to set email alerts
|

Platelets, coagulation and fibrinolysis in breast cancer progression

Abstract: The progression of breast cancer from early-stage to metastatic disease results from a series of events during which malignant cells invade and travel within the bloodstream to distant sites, leading to a clonogenic accumulation of tumor cells in non-breast tissue. While mechanistically complex, an emerging literature supports hemostatic elements as an important patient factor that facilitates the metastatic potential of breast cancer. Hemostatic elements involved include platelets, coagulation, and fibrinolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 81 publications
3
117
0
1
Order By: Relevance
“…Cancer cells were shown to have the ability to interact with platelets in vitro several decades ago (19)(20)(21)(22). Furthermore, the interaction between circulating tumor cells (CTCs) and circulating platelets is now recognized as a hallmark of the metastatic potential of cancer (6,8). Recent studies have demonstrated that the presence of platelet aggregation around tumor cells can be detected both in the circulation and in primary tumor cells in patients with pancreatic cancer (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells were shown to have the ability to interact with platelets in vitro several decades ago (19)(20)(21)(22). Furthermore, the interaction between circulating tumor cells (CTCs) and circulating platelets is now recognized as a hallmark of the metastatic potential of cancer (6,8). Recent studies have demonstrated that the presence of platelet aggregation around tumor cells can be detected both in the circulation and in primary tumor cells in patients with pancreatic cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, the smallest anucleate hematopoietic cells, are now recognized as key regulators of tumor progression and metastasis (6)(7)(8). In the circulation, platelet aggregation protects cancer cells from shear stress and immune surveillance through the formation of a platelet cloak.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we summarize the recent progress in breast cancer biology associated with aberrant coagulation mechanisms. In particular, we focus on the TF-fVII pathway, among the multiple coagulation mechanisms, because breast cancer phenotypes associated with platelets and fibrinolysis have been extensively reviewed [17] . We also describe the mechanisms underlying TF and fVII overexpression and how their functions may be regulated in breast cancer cells.…”
Section: Topic Highlightmentioning
confidence: 99%
“…Platelets are important in tumour cell migration [3] and experimental data have shown that aspirin can inhibit platelet-induced adhesion of circulating tumour cells [4], and prevent metastases formation [5]. In breast cancer specifically, both in vitro and animal models demonstrate anti-angiogenic [6] and pro-apoptotic [7] effects for aspirin, as well as the suppression of tumour cell extravasation and tissue invasion [8].…”
Section: Introductionmentioning
confidence: 99%